2013
DOI: 10.12988/asb.2013.3210
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 8-week aerobic exercises on serum levels of cell adhesion molecules among middle-aged women

Abstract: Introduction: Cell adhesion molecules and inflammation mediators ramp up the activities of vascular endothelial, and researchers consider them as new predictive markers in cardiovascular diseases. With decreasing inflammation, physical 280 Seyyed Mahmoud Hejazi et al. activity can reduce coronary heart disease (CHD) risk. The study was aimed to investigate the effect of one period of selective aerobic training on serum levels of ICAM-1, VCAM-1, and E-selectin in middle-aged women. Methods: Twenty-four healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…One of the important finding of the present study was the reduction in serum levels of ICAM-1 and E-Selectin due to aerobic exercise. The changes in serum levels of ICAM-1 and E-selectin in response to aerobic exercise reported conflictingly in various research findings but Studies have shown that ICAM-1 and E-selectin have a similar relationship [ 15 17 , 22 24 ]. Much evidence suggests that inflammation plays important role in the process of atherosclerosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important finding of the present study was the reduction in serum levels of ICAM-1 and E-Selectin due to aerobic exercise. The changes in serum levels of ICAM-1 and E-selectin in response to aerobic exercise reported conflictingly in various research findings but Studies have shown that ICAM-1 and E-selectin have a similar relationship [ 15 17 , 22 24 ]. Much evidence suggests that inflammation plays important role in the process of atherosclerosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that physical activity can reduce the resting levels of these cytokines by reducing obesity, leptin and increasing the adiponectin and insulin sensitivity [ 16 , 28 30 ]. Exercise training can effect on adhesion molecules and endothelial injuring markers by decreasing of inflammatory factors particularly NF-KB and IL-1B [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation plays a main role in the development and progression of atherosclerosis (1, 2) through endothelial activation and expression of adhesion molecules on the surface of activated endothelial cells (3). Excessive and chronic production of inflammatory cytokines disrupts cardiac contraction and may induce hypertrophy and apoptosis of cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%